An Arthroscopic "Inlay" Bristow Procedure With Suture Button Fixation for the Treatment of Recurrent Anterior Glenohumeral Instability: 3-Year Follow-up. Issue 11 (September 2020) - Shao, Zhenxing; Song, Qingfa; Cheng, Xu; Luo, Hao; Lin, Lin; Zhao, Yuqing; Cui, Guoqing
Background: Coracoid graft positioning, fixation, and bone union are key factors affecting the clinical outcomes of Bristow and Latarjet procedures. We developed an arthroscopic "inlay" Bristow procedure based on the "mortise-tenon" joint structure concept using suture button fixation to achieve more stable fixation and better bone union of the graft. Purpose: To evaluate the positioning of the coracoid graft, bone union rate, and clinical outcomes of this arthroscopic inlay Bristow procedure with suture button fixation. Study Design: Case series; Level of evidence, 4. Methods: A total of 62 patients who received the arthroscopic inlay Bristow procedure with suture button fixation between June 2015 to June 2016 were eligible for inclusion, and 56 patients who met the inclusion criteria were enrolled in this study. Radiological assessment on 3-dimensional computed tomography scan was performed preoperatively, immediately after the operation, and postoperatively at 3 months, 6 months, 1 year, and the final follow-up. Pre- and postoperative clinical results were also assessed. Results: A total of 56 patients were included in this study. The mean ± SD follow-up time was 36.1 ± 3.7 months. Coracoid grafts (middle point) were positioned at 4 o'clock (range, 123.8°± 12.3°) in the sagittal view. In the axial view, 94.6% (53/56) of the graft positioning was measured as flush and 5.4% (3/56) as medial. Neither lateral nor too medial positioning was noted. The bone union rate was 96.4% at final follow-up. The mean visual analog scale score for pain during motion, American Shoulder and Elbow Surgeons score, and Rowe score all improved significantly after surgery—from 4.8 ± 2.6 to 1.1 ± 1.0, 69.2 ± 12.5 to 92.5 ± 7.0, and 33.5 ± 12.1 to 96.0 ± 4.9 at last follow-up, respectively. Almost all patients (98%; 55/56) returned to sports within 1 year after surgery at the same or higher level as compared with their preinjury performance. The mean subjective value for sports participation was 90.3% ± 7.1% (range, 70%-100%) as compared with the normal shoulder. The overall complication rate was 3.6%. No degenerative changes were noted in any patients. Conclusion: This study reported the first series of an inlay Bristow procedure with suture button fixation for recurrent shoulder dislocation, providing a satisfactory union rate and excellent graft positioning with a low complication rate. The mortise-tenon joint structure can provide excellent graft fixation and healing, while using suture button fixation instead of screw fixation could reduce osteolysis and complications related to hardware implantation.